A comprehensive review of the features of self‑compacting rubberized concrete in the fresh and hardened states - Islam, Md. Toriqule; Hasan, Md Kamrul; Zaied, Khalid; Fadzil, Mat Yahaya (Springer Nature, 2022)
The rapid growth of urbanization and revolutionary improvement in the transportation industry paves the way for boosting tire production and generating a massive amount of waste tires every year. Waste tire disposal and proper maintenance have become a global concern because of the harmful chemical composition that conveys the potential to create an ecological imbalance that jeopardizes the world. One of the most powerful options is to ease the global problem by using recycled waste tires in the construction sector, especially in self-compacting concrete (SSC), as partial substitutes for natural aggregates, which lessens natural resource usage and eventually increases the long-term growth of economic efficiency in the construction industry. This study summarizes, compares, and draws general conclusions from over 100 independent studies in terms of the fresh and hardened state properties of rubberized concrete (RuC) to highlight and confirm the critical characteristics of the material. The results show that concrete containing crumb rubber (CR) reduces fresh and mechanical properties, where the inclusion of supplementary cement materials (SCM) such as slags, Metakaolin, and various fibers, such as steel fibers, synthetic fibers, and pre-treatment of rubber aggregates (RA) can successively enhance the fresh and hardened properties of self-compacting rubberized concrete (SCRC). Moreover, the inclusion of waste tires as partial replacement of natural aggregates of varying levels and their positive and negative impact on SCRC’s fresh and hardened properties have been reviewed.